Unusual cranial infection caused by Citrobacter Koseri. (2nd January 2020) - Das, Suparna; Ross, Nicholas
Abstract: A 60-year-old female had a frontal bone intraosseous meningioma resected 10 years previously. On follow up CT head, an enlarging intraosseous frontal bone lesion was noted. This was thought to be a recurrent frontal meningioma. Intraooperatively, she was found to have an abscess deep to the cranioplasty.